Comparison between preterm and full term neonatal cord selenium in correlation to maternal serum selenium levels - Gihan M. Bebars; Bothina A. Kamel; Emad Allam (SpringerOpen, 2018)
Background: Lower concentrations of selenium and glutathione peroxidase activities have been reported in pregnant women. An exposure to a high oxygen concentration at birth, an infection, inflammation, and a deficient antioxidant system make the newborn more susceptible to oxidative stress that can result in bronchopulmonary dysplasia, retinopathy of prematurity, persistent ductus arteriosus, necrotizing enterocolitis, intracranial hemorrhage, and hypoxic ischemic encephalopathy, especially in extremely low-birth-weight infants. Aim: The current study aimed at the detection and comparison of maternal serum and neonatal umbilical cord selenium levels. Methods: A prospective study on 80 mothers and their healthy neonates (40 full term and 40 preterm) enrolled over the period from June to December 2016. Selenium concentrations were measured in the maternal serum and umbilical cord using a spectrophotometer. Results: A significantly higher mean selenium level was detected in term neonates than preterm neonates (P = 0.015) with no gender difference but the difference in selenium concentration between their mothers was not significant. No significant relations found between maternal serum selenium levels and maternal age, weight, height, BMI or pregnancy weeks. The maternal serum selenium was positively correlated with the cord selenium in full-term group (r = 0.59 & P = 0.006). Significantly positive correlations between umbilical cord selenium levels in both full-term and preterm neonates with their gestational age and birth weight. Conclusion: This study indicated that cord Se concentration was different in term and preterm neonates being higher in full terms, so we recommend selenium supplementation to preterm neonates and their mothers to avoid sequelae of selenium deficiency on their health and to reach the levels obtained in full term neonates.